2016
DOI: 10.1103/physreva.93.049904
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Quantum renormalization group of theXYmodel in two dimensions [Phys. Rev. A92, 032327 (2015)]

Abstract: There is a typing mistake in the expression of γ 4 given in the Appendix. The actual expression is γ (5+α 1 +γ 2) 2 √ 2α 2 , which is used in the calculations throughout the paper. In the caption of Fig. 6, "(see Fig. 6)" should read "(see Fig. 4)".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 0 publications
7
20
0
Order By: Relevance
“…It reaches to maximum value at the critical point and it can be seen that this maximum value is smaller in three dimensions as compared to its two-dimensional counterpart. Likewise scenario can be seen for the qualitative and the quantitative behavior of the concurrence in the XY model, as we go from the lower to higher dimensions [10,31]. It is the monogamy that limits the entanglement shared among the number of neighbor sites [19].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…It reaches to maximum value at the critical point and it can be seen that this maximum value is smaller in three dimensions as compared to its two-dimensional counterpart. Likewise scenario can be seen for the qualitative and the quantitative behavior of the concurrence in the XY model, as we go from the lower to higher dimensions [10,31]. It is the monogamy that limits the entanglement shared among the number of neighbor sites [19].…”
Section: Introductionmentioning
confidence: 94%
“…1.) to obtain the effective Hamiltonian which has similar structure as that of the original Hamiltonian. From the previous studies of the XY model [10,11,31], it is found that in the renormalization process, the projection operator constructed from the degenerate ground states of the block works well for obtaining the effective Hamiltonian in the renormalized Hilbert space of spin -1/2 particle. The degenerate ground eigenstates can only be obtained if we consider the blocks containing odd number of spins in any spatial dimensions.…”
Section: Qrg Implementationmentioning
confidence: 99%
See 3 more Smart Citations